RUMAH CUKUP (RUCUP): Farmer Households Community Development Program as a Solution for Increasing Food Availability on Kemaro Island, Palembang City - Nurilla Elysa Putri; Muhammad Yamin; Muhammad Izzudin (Community Development Journal, 2023)
National food security begins with the provision of food in the smallest locations, mainly villages and sub-districts. Kemaro Island is part of Palembang City, which is administered by Kelurahan 1 Ilir Palembang City. Due to limited accessibility, circumstances for providing basic requirements, particularly food and clean water, are severely constrained. Foods such as vegetables and fruit are still scarce in this area, particularly milk, cereals, and other nutritional foods. Thus, it is vital to undertake measures to boost the availability and accessibility of food for independent home farmers in this region, given the territory's status as a distinct island. Efforts to enhance the food security of farmer households on Kemaro Island can be accomplished through the implementation of a participatory in Rumah Cukup (Rucup) program. Extension is conducted as a coaching and mentoring activity aimed at enhancing the food security of farmer households through the Rumah Cukup (Rucup) initiative, in which farmer households cultivate a variety of horticulture commodities.